DINÂMICA EM GRUPOS SUCESSIONAIS DA FLORESTA OMBRÓFILA ABERTA SUBMONTANA NA REGIÃO NORTE DO MATO GROSSO - BISPO, LILIANE BARBOZA (2023)
Brazil has six types of biomes, each one has its natural diversity, particularity and beauty, namely: Amazon, Cerrado, Caatinga, Atlantic Forest, Pantanal and Pampa. The Amazon Forest is the largest tropical forest in the world and in Brazilian territory and occupies approximately 49.0% of the national territory, which is equivalent to an area of 4.2 million km². This biome is mainly made up of dense and open forests, home to the largest hydrographic network in the world. The objective of this study was to analyze the existing vegetation in a fragment of the Submontane Open Rainforest (FOAS), aiming to understand structure and successional dynamics, denoting its ecological importance and providing information that helps in the application of sustainable forest management practices. The study was carried out in the native vegetation area, in the municipality of Alta Floresta-MT, Brazil. A 1 hectare sampling unit was installed in the study area, subdivided into 25 sampling subunits of 400 m² each. In this sampling area, all individuals with DBH ≥ 5 cm were taxonomically identified and measured. The first measurement was carried out in 2018. On the second occasion, in 2021, the botanical material of the recruited species was collected and all individuals were remeasured and counted. In the sampling unit, a total of 905 ind/ha-¹, 200 species were recorded, where the families with the greatest specific richness were Moraceae with (25 sp.). The most important species in the study was Bertholletia excelsa (Lecythidaceae), presenting IVI with 8.34%. Diversity was considered high, with 4.60 ind nats-1. The forest dynamics presented a balance between the mortality and entry rates, being 1.58% and 1.54% per year respectively. The predominance of individuals belonging to the late secondary group suggests that the area is in an intermediate to climax succession stage. This scenario is reinforced by the fact that the FOAS fragment in question has a high diversity of species, which are in dynamic successional balance. Furthermore, the history of absence of disturbances in the area strengthens the hypothesis that it is in a forest stage at the succession climax level.